2020
DOI: 10.1109/access.2020.2966247
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Design of Tightly Coupled Dipole Array Using an Equivalent Circuit-Based Approach

Abstract: This paper proposes an efficient and systematic design approach for tightly coupled dipole array (TCDA) designs. In this approach, the radiator structure and feeding structure are designed and optimized based on their equivalent circuit models (ECM) respectively. A novel ECM is proposed to accurately describe the impedance characteristics of the radiator structure with dual-diamond dipoles. The proposed ECM of the radiator structure keeps its accuracy for variable design parameters. The ECM of the proposed fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…He also showed that using negative inductance works best. A review of articles and books demonstrates that much has been done with both approaches [12][13][14][15][16][17][18][19][20][21]. To properly evaluate this issue, which can be a good guide for choosing the optimal structure in the design of broadband arrays, it is necessary to have a thorough analytical or numerical study of this issue.…”
Section: Introductionmentioning
confidence: 99%
“…He also showed that using negative inductance works best. A review of articles and books demonstrates that much has been done with both approaches [12][13][14][15][16][17][18][19][20][21]. To properly evaluate this issue, which can be a good guide for choosing the optimal structure in the design of broadband arrays, it is necessary to have a thorough analytical or numerical study of this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The wideband antenna array can be achieved by a wideband tightly coupled antenna array, [11][12][13][14][15][16][17][18][19][20][21][22][23] which can avoid the deterioration of radiation characteristics at high frequencies resulting from wide array spacing. At present, there are many achievements in wideband tightly coupled antenna array, mainly in the form of printed dipole.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the continuous current sheet concept has been extensively explored for antenna array developments 13‐15 . Based on this concept, different types of arrays have been proposed, including the connected arrays, 16 the planar ultra‐wideband modular antennas (PUMAs), 17‐19 and the tightly coupled dipole arrays (TCDAs) 20‐30 . The TCDA has emerged as an attractive candidate for ultra‐wideband and low‐profile applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, these TCDAs are difficult to achieve more than a decade bandwidth. To further broaden the bandwidth, many kinds of resistive structures are introduced between dipole elements and the array ground plane, for example, resistive rings, 24‐27 resistive sheets (R‐Sheet), 28,29 and frequency selective surface (FSS) R‐Sheet 30 . In a word, the studies in References 20–30 are important for the profile reduction and bandwidth improvement of TCDAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation